2021
DOI: 10.1007/s11104-021-05070-0
|View full text |Cite
|
Sign up to set email alerts
|

Response of fungal communities to fire in a subtropical peatland

Abstract: Purpose: Wild re, an increasing disturbance in peatlands, could dramatically change carbon stocks and reshape plant/microbial communities, with longlasting effects on peatland functions. Soil fungi are important in controlling the belowground carbon and nutrient cycling in peatlands; however, the impact of altered re regimes on these fungi is still unclear.Methods: Here we assessed fungal abundance, composition, and diversity across four soil depths (0-5 cm, 6-10 cm, 11-15 cm, 16-20 cm) under lowintensity and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 97 publications
0
5
1
Order By: Relevance
“…An unexpected taxon detected in our study, Archaeorhizomycete fungi, does not form above-ground sporocarps so are not typically known as a pyrophilous taxon, however, recent studies that have used DNA metabarcoding have found these fungi to be abundant following wildfire 38 , 71 . Archaeorhizomycete fungi were initially described from marker gene studies of soil, found to have a global distribution, and later two species were isolated as slow-growing cultures 72 74 .…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…An unexpected taxon detected in our study, Archaeorhizomycete fungi, does not form above-ground sporocarps so are not typically known as a pyrophilous taxon, however, recent studies that have used DNA metabarcoding have found these fungi to be abundant following wildfire 38 , 71 . Archaeorhizomycete fungi were initially described from marker gene studies of soil, found to have a global distribution, and later two species were isolated as slow-growing cultures 72 74 .…”
Section: Discussioncontrasting
confidence: 50%
“…Archaeorhizomycete fungi were initially described from marker gene studies of soil, found to have a global distribution, and later two species were isolated as slow-growing cultures 72 74 . In a study of soil fungi from a subtropical peatland, Archaeorhizomycete fungi had high relative abundance responding to low- and high-intensity fire at various soil depths 71 . Another study has specifically linked Archaeorhizomycete fungi with decreased soil water repellency and increased soil moisture content, following wildfire in a European pine stand 38 .…”
Section: Discussionmentioning
confidence: 99%
“…An unexpected taxon identified in our study, Archaeorhizomycete fungi, does not form above-ground sporocarps so are not typically known as a pyrophilous taxon, however, recent studies that have used DNA metabarcoding have found these fungi to be abundant following wildfire. 39,72 Archaeorhizomycete fungi were initially described from marker gene studies of soil, found to have a global distribution, and later two species were isolated as slow-growing cultures. [73][74][75] In a study of soil fungi from a subtropical peatland, Archaeorhizomycete fungi had high relative abundance responding to low-and high-intensity fire at various soil depths.…”
Section: Discussionmentioning
confidence: 99%
“…[73][74][75] In a study of soil fungi from a subtropical peatland, Archaeorhizomycete fungi had high relative abundance responding to low-and high-intensity fire at various soil depths. 72 Another study has specifically linked Archaeorhizomycete fungi with decreased soil water repellency and increased soil moisture content, following wildfire in a European pine stand. 39 In this study, we detected Archaeorhizomyces SVs as bioindicators of establishment and mature stand development stages, representing the 11 th most abundant class of fungi based on relative read abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Both the soil properties and above‐ground vegetation can influence the soil fungal communities. With the forest recovery after fire, the above‐ground vegetation becomes progressively more diverse, and both the mixing of plant litter and the interaction of root exudates may be important factors causing significant changes in soil physicochemical properties, such as pH, which may lead to an altered fungal community and function (Glassman et al, 2017; Tian et al, 2021). The soil vertical gradient itself is an important determinant of fungal community composition and dispersal (Lindahl et al, 2007; Upton et al, 2020).…”
Section: Discussionmentioning
confidence: 99%